Examination of undisturbed acoustic emission generated by experimentally modelled two-body abrasive wear events. (January 2020) - Haas, Michael; El Syaad, Karim; Cihak-Bayr, Ulrike; Pauschitz, Andreas; Gröschl, Martin
Abstract: Acoustic emission (AE), i.e. elastic waves caused by rapid release of elastic energy, is sensitive to wear mechanisms. However, the nature of wear is complex and, in addition, reflections of AE waves at the boundaries of the propagation medium cause interferences and complicate the correlation of AE features and wear events. To overcome these problems, an experiment has been established which experimentally models temporally short two-body abrasive wear events. The aim was to reveal the relationship between wear and associated AE. The RMS value of AE showed a correlation with the contact area of the experimentally modelled wear events. Normalized mean values of specific frequency ranges of Fourier transformed AE are applicable for distinction of the type of modelled wear. Highlights: An setup was built, able to generate modelled single 2-body abrasive wear events. RMS-values of acoustic emission correlate with the contact area. PCA is appropriate for identification of distinctive frequency ranges of AE. The type of modelled wear can be distinguished by weights of frequency ranges.